Contextualizing Peace in Islamic Traditions: Challenging Cultural Hegemony (In Factis Pax: Journal of Peace Education and Social Justice, 2011)
Representations of Islam and Muslims, perpetuated in popular media and elsewhere, continue to paint a picture of a people and religion plagued by violence, oppression, and fanaticism. These dominant images often include various groups and individuals who have resorted to extreme forms of violence in the name of ideological interpretations of Islam, or subservient,shrouded women in dark veils. There is a stark contrast, however, between the dominantly projected hegemonic discourse on Islam, and the realities of the strides being made by individuals in the field of peacebuilding who derive impetus for the transformation and negation of violent conflict from an interpretation of Islamic faith, which locates peace as central to the goal of human history.